A Glimpse Into the Magnet® Program Office: The High-Performing Senior Magnet® Program Analyst Team. (June 2021) - George, Nicole
Abstract : The Magnet Recognition Program ® has a dedicated team of RNs and non-RNs who are committed to advancing nursing and supporting healthcare organizations on their Magnet ® journeys. Healthcare organizations who are either Magnet-designated or applicants for Magnet designation regularly communicate with the various members of the Magnet program office team. This perspective will highlight the roles of the senior Magnet program analysts and the assistant director of Magnet program operations.